Pengembangan Masyarakat melalui Usaha Mikro Kecil untuk Meningkatkan Religiusitas Remaja Kabupaten Bogor - Yuliana Cita Siti Hijria (Fakultas Dakwah IAIN Jember, 2022)
Da'wah method is a method or method used by a da'wah actor. Communicating Islamic Da'wah teachings by conveying da'wah messages, this method plays a very important role. However, if it is conveyed in the wrong way, this role can be rejected by the recipient of the message. In Bogor Regency, there are still many teenagers who are not good (disgraceful) as is the case for teenagers who do not respect their parents, there are still many teenagers who like to talk dirty, there are still many Teenagers who don't respect their neighbors, there are still many teenagers who don't have a forgiving spirit, as a result, fights often occur that give rise to trivial conflicts. However, there is a community that cares about the morals of youth in Bogor Regency, which then provides a good environment and impact on the surrounding youth by way of gentle preaching. How to approach the habits of teenagers who like to hang out by facilitating them by creating an Islamic cafe. And in cafe 99, researchers will examine more deeply how the stages of da'wah can have a significant impact on the lives of local youth. The practice of da'wah is by means of takwin, tandzim, and release. Also with Stages: Question and answer sessions, discussions, examples and optimal use of technical possibilities, Communicate the talents and interests of young people: sport and art. In addition, various supports are required. Efforts such as collaboration with other organizations related agencies, including community leaders, government, teachers, youth themselves. And all that is done by synergized Muslim youths at cafe 99 Bogor Regency as an effort to improve morals with Shari'a morals in surrounding teenagers.